'The wandering Missionary, Tang-goo': G. Herbert Rodwell's creation of the first Pākehā Māori in published novels. Issue 2 (19th January 2023) - Chandler, David
In 1846, in his serialized novel Woman's Love: A Romance of Smiles and Tears!, G. Herbert Rodwell (1800–52) introduced a Pākehā Māori character, 'the wandering Missionary, Tang-goo'. Although Jules Sébastien César Dumont d'Urville (1790–1842) had included a Pākehā Māori in his earlier novel, Les Zélandais: Histoire Australienne, written in 1824–25, this remained unpublished, and therefore Rodwell's Tang-goo appears to be the first such character in a published novel. Tang-goo is a richly imaginative conception drawing on various sources, including the Pākehā Māori who had come to London, a 'White Father' character in G. P. R.James's 1835 novel, The Gipsy, the Native American category of 'medicine men', the experiences of missionaries in New Zealand, especially Samuel Marsden's 1820 travels, and the Biblical John the Baptist. For much of Rodwell's novel, Tang-goo is taken to be authentically Māori and as such seems to be a fantastical representation of Britain's civilizing influence in New Zealand. The novel's late revelation that Tang-goo was born an English nobleman explodes such a fantasy and also subverts the stereotyped negative portrayals of Pākehā Māori in missionary literature. Tang-goo knows himself to be a unique figure; his creation of a Māori identity is complete only once he is dead.